2020
DOI: 10.1155/2020/8868638
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Deep Geofluids in the Enrichment of Sedimentary Organic Matter: A Case Study of the Late Ordovician-Early Silurian in the Upper Yangtze Region and Early Cambrian in the Lower Yangtze Region, South China

Abstract: Organic matter is the material basis for shales to generate hydrocarbon, as well as the main reservoir space and seepage channel for shale gas. When the thermal evolution degree is consistent, the organic carbon content in present shales is subject to the abundance of primitive sedimentary organic matter. Deep geofluids significantly influence the sedimentary organic matter’s enrichment, but the mechanism remains unclear. This paper is aimed at determining how hydrothermal and volcanic activities affected the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…In particular, the initial productivity of waterbody can be characterized by the 14 Geofluids nutrient richness and organic carbon flux of surface water, and the change of initial productivity plays a key role in the accumulation of organic matter. The Ba content is an indicator widely used to reflect the paleoocean bioproductivity [56][57][58][59][60]. There is a high concentration of SO 4 2-ions reoxidized by H 2 S on the surface of decayed organic matter.…”
Section: Paleoproductivity Control On Deposition Of Thementioning
confidence: 99%
“…In particular, the initial productivity of waterbody can be characterized by the 14 Geofluids nutrient richness and organic carbon flux of surface water, and the change of initial productivity plays a key role in the accumulation of organic matter. The Ba content is an indicator widely used to reflect the paleoocean bioproductivity [56][57][58][59][60]. There is a high concentration of SO 4 2-ions reoxidized by H 2 S on the surface of decayed organic matter.…”
Section: Paleoproductivity Control On Deposition Of Thementioning
confidence: 99%
“…Previous studies on lacustrine fine-grained rocks have shown that the sedimentation process of lacustrine finegrained rocks with frequent lithological changes is closely related to the changes in the paleoenvironment. The evolution of the paleoenvironment tends to lead to the changes in the chemical composition of rocks, mineral composition, content of organic matter, rock type, and other aspects [50][51][52][53][54][55][56][57][58], so indicators such as geochemistry and mineral composition can be used to study the paleoclimate, paleowater depth, paleoredox conditions, paleosalinity, paleoproductivity, and other aspects [56][57][58][59][60]. In this paper, various indicators for the changes in the sedimentary environment were selected to further explore and confirm that the sedimentary environment of lacustrine fine-grained rocks in the lower Es3 submember of the Paleogene Shahejie Formation in Well Fanye-1 of the Dongying sag was affected by the Milankovitch cycle.…”
Section: Environmental Response Characteristics Of the Milankovitch Cyclementioning
confidence: 99%
“…However, from the perspective of the Niutitang shale in Chongqing, its thermal maturity is much higher than that in the Jingyan, Yichang, and Guizhou regions, while there are no OM pores of the Niutitang shale in Chongqing. However, other parameters such as TOC content, mineral composition, and kerogen type of the Niutitang shale reservoirs in the four regions (Jingyan, Chongqing, Yichang, and Guizhou) have similar characteristics [2,6,7,40,42,[48][49][50][51]. Therefore, thermal maturity is the key factor to control the OM pore development.…”
Section: Geofluidsmentioning
confidence: 99%